Challenges to Community Participation in Gaza Strip Municipalities - Enshassi, Adnan; Kullab, Ahmed; AlKilani, Suhair; Sundermeier, Matthias (International Journal of Sustainable Construction Engineering and Technology, 2016)
Community participation in municipalities' decisions and long planning processes ensures their full engagement in determining their own developmental needs. Therefore, identifying the challenges for community participation is considered as a crucial aspect for successful governance and service delivery in the local municipalities of governments. The aim of this paper is to identify and assess the challenges to community participation in Gaza Strip municipalities in Palestine. Ten groups of challenges, which comprise 44 factors for community participation in Gaza Strip municipalities were identified from the literature review and modified according to the pilot study. A structured questionnaire survey was employed in this study. Relative Importance Index (RII) was used to determine the ranks of the main groups of challenges and its corresponding factors, followed by a parametric test that is analysis of variance (One-Way ANOVA) to test five developed hypotheses. The findings of this paper revealed that shortage of skills was the most significant challenge group to community participation.. The second most significant challenge group was the financial challenges. Â The third significant group of challenges to community participation was lack of interest and support due to limited support from city council and lack of transparency. The findings revealed agreement among all participants in the most significant challenges for community participation, with one exceptional, where there was disagreement on the rating the main groups of the challenges in terms of the population categories.Â